2018
DOI: 10.1101/448035
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bridging the divide: bacteria synthesizing archaeal membrane lipids

Abstract: Archaea synthesize membranes of isoprenoid lipids that are ether-linked to glycerol, while Bacteria/Eukarya produce membranes consisting of ester-bound fatty acids. This dichotomy in membrane lipid composition or 'lipid divide' is believed to have arisen after the Last Universal Common Ancestor (LUCA). A leading hypothesis is that LUCA possessed a 'mixed heterochiral archaeal/bacterial membrane', however no natural microbial representatives supporting this scenario have been shown to exist today. Here, we demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 75 publications
1
22
0
Order By: Relevance
“…This elicits the question of why members of the bacterial FCB superphylum would carry genes to synthesize the lipids typically associated with archaeal membranes. Whether these genes were acquired horizontally at the base of the group or were always there since LUCA and have since been lost in all other groups, it remains an unusual example of heterotypic membranes that calls for an explanation.…”
Section: Membrane Proteins As Drivers Of the Lipid Dividementioning
confidence: 90%
See 3 more Smart Citations
“…This elicits the question of why members of the bacterial FCB superphylum would carry genes to synthesize the lipids typically associated with archaeal membranes. Whether these genes were acquired horizontally at the base of the group or were always there since LUCA and have since been lost in all other groups, it remains an unusual example of heterotypic membranes that calls for an explanation.…”
Section: Membrane Proteins As Drivers Of the Lipid Dividementioning
confidence: 90%
“…A recent study reports that members of the bacterial Fibrobacteres/Chlorobi/Bacteroidetes (FCB) superphylum contain an almost complete set of genes for synthesizing archaeal membrane lipids, in addition to the traditional bacterial lipids . The initial results came from a metagenomic study of strains that are yet to be cultured in the laboratory, but were then shown to extend to multiple members of the FCB superphylum sequenced previously.…”
Section: Bacteria With Archaeal Lipids Are Found In Naturementioning
confidence: 99%
See 2 more Smart Citations
“…In these species lacking G1PDH, it is unclear whether GGGPS and DGGGPS are active and if so, what they are used for; one possibility is that they catalyse the reverse reaction, catabolising archaeal lipids as an energy source. However, a very recent report (Villanueva et al 2018) has shown that the GGGPS and DGGGPS genes from one FCB lineage, Cloacimonetes, support the production of archaeal-type membrane phospholipids and a mixed membrane when heterologously expressed in E. coli. This suggests that both E. coli and perhaps Cloacimonetes have an alternative, as yet unknown mechanism for making G1P, and that some FCB members may have mixed archaeal and bacterial membranes Orthologues of the canonical bacterial genes are less widespread in Archaea (Table 1).…”
Section: Resultsmentioning
confidence: 99%